2019
DOI: 10.1016/j.devcel.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Global Neural Crest Gene Regulatory Network In Vivo

Abstract: SummaryPrecise control of developmental processes is encoded in the genome in the form of gene regulatory networks (GRNs). Such multi-factorial systems are difficult to decode in vertebrates owing to their complex gene hierarchies and dynamic molecular interactions. Here we present a genome-wide in vivo reconstruction of the GRN underlying development of the multipotent neural crest (NC) embryonic cell population. By coupling NC-specific epigenomic and transcriptional profiling at population and single-cell le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
185
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(197 citation statements)
references
References 115 publications
(180 reference statements)
12
185
0
Order By: Relevance
“…Our findings of upregulated/downregulated genes coincide in larger proportion with their migratory gene profiling. Further support that our array was focused of DRG transition is that we did not observe TFAP2B, Snai2, Zeb2, and Lmo4 (bona fide NC and EMT factors) in our array (Williams et al, 2019).…”
Section: Little Is Known About the Cessation Of Ncc Migrationsupporting
confidence: 63%
See 1 more Smart Citation
“…Our findings of upregulated/downregulated genes coincide in larger proportion with their migratory gene profiling. Further support that our array was focused of DRG transition is that we did not observe TFAP2B, Snai2, Zeb2, and Lmo4 (bona fide NC and EMT factors) in our array (Williams et al, 2019).…”
Section: Little Is Known About the Cessation Of Ncc Migrationsupporting
confidence: 63%
“…Recently, Williams et al (2019) have shown a global NCC GRN profiling of genes involved in their development. Our findings of upregulated/downregulated genes coincide in larger proportion with their migratory gene profiling.…”
Section: Little Is Known About the Cessation Of Ncc Migrationmentioning
confidence: 99%
“…Sox-10 is a member of the SoxE subclass of high-mobility-group domain-containing Sox transcription factors, which plays a critical role in the maintenance of the progenitor/stem cell state of neural crest cells (Hong & Saint-Jeannet, 2005;Weider & Wegner, 2017). It exists in all vertebrates examined so far, from lamprey to human, and it is expressed at all axial levels by neural crest cells at the time of their segregation from the neural tube and during their subsequent migration to their target sites (Hockman et al, 2019;Williams et al, 2019). In culture, Sox-10 shows essentially the same expression pattern in neural crest cells as in the embryo.…”
Section: Characterizing Neural Crest Cell Phenotype In Culture Usingmentioning
confidence: 99%
“…Current Protocols in Cell Biology Numerous other possible markers for neural crest cells have been reportedly used in vivo or in vitro, such as the p75 low affinity nerve growth factor receptor (p75-NGFR), nestin, Msx-1, Twist-1, Pax-3, AP-2α, cMyc, Id-1, or Ets-1, to name a few (Dupin & Sommer, 2012;Soldatov et al, 2019;Williams et al, 2019). Notwithstanding their interest and potential, these markers have been less frequently used or simply cannot be used to characterize avian trunk neural crest cells in culture.…”
Section: Of 25mentioning
confidence: 99%
See 1 more Smart Citation